1981
DOI: 10.1073/pnas.78.10.6139
|View full text |Cite
|
Sign up to set email alerts
|

Uninfected cell polymerase efficiently transcribes early but not late herpes simplex virus type 1 mRNA.

Abstract: The sequences ofthe DNAs encoding the 5' ends of one early and one late herpes simplex virus type 1 mRNA were analyzed, and the 5' ends of these mRNA species were precisely located. Neither mRNA species is spliced and the noncoding strand ofthe DNA contains recognizable T-A-T-A and C-A-T boxes upstream from their respective 5 The question ofwhat factors control the temporal regulation of DNA virus gene expression is an active field ofresearch. The development of faithful uninfected cell transcription systems (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
50
0

Year Published

1984
1984
1987
1987

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 21 publications
4
50
0
Order By: Relevance
“…We assume that this also is the case with the unmodified VP5 promoter. This conclusion is in agreement with the data of Frink et al (12), who demonstrated that the unmodified VP5 promoter is not recognized by an in vitro transcription system prepared from uninfected HeLa cells. It is not obvious what features account for the inactivity of the VP5 promoter in uninfected cells.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We assume that this also is the case with the unmodified VP5 promoter. This conclusion is in agreement with the data of Frink et al (12), who demonstrated that the unmodified VP5 promoter is not recognized by an in vitro transcription system prepared from uninfected HeLa cells. It is not obvious what features account for the inactivity of the VP5 promoter in uninfected cells.…”
Section: Discussionsupporting
confidence: 83%
“…This current classification may be somewhat oversimplified, because some late genes (e.g., that for VP5) are detectably expressed before replication (12), whereas others are not (18). In the former case, (the so-called 3--y class) it seems possible that the observed pattern of transcription can be accounted for by two distinct processes: first, the 13-y promoters are activated by ICP4 with delayed-early kinetics and second, template amplification, the result of DNA replication, boosts the level of expression further.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the transcript specifying 24K may have been present in low abundance, and therefore not detected by Costa et al (1981). Earlier versions of the DNA sequence encoding the carboxy terminus of 24K and the non-coding region at the 5' end of the 149K gene in HSV-1 strain KOS (Frink et aL, 1981 ;Costa et aL, 1984) contain several errors which were corrected without comment by Costa et al, (1985a). The remaining differences between the HSV-1 strain 17 and strain KOS sequences are located between the 24K and 149K coding regions, and thus may represent genuine sequence differences between the two strains.…”
mentioning
confidence: 99%